The Synthesis of Immobilised Reagents Based on a Polymerised Triphenylphosphine Scaffold for Use in Flow Chemistry Applications - Panayides, Jenny-Lee (University of Pretoria, 2020)
Thesis (PhD (Chemistry))--University of Pretoria, 2020.